Map with flow-net diagram showing movement of water in the Lee Formation in the Paint Creek drainage basin in parts of Johnson, Magoffin and Morgan Counties, Eastern Coal Field region, Kentucky [peta] (Washington, D C : Department of the Interior, 1969)
PSZJBL